The Perception of Deaf People Towards the Use of Hearing Aids - Elsa Efrina; Achmad Hufad; Endang Rochyadi; Asep Bayu Dani Nandiyanto; Arisulmahdi Arisulmahdi; Rila Muspita (Universitas Negeri Padang, 2023)
This article discusses the perception of the deaf in using hearing aids. Based on observations, not all deaf people use hearing aids, even though they have experience using hearing aids. A descriptive quantitative approach was used to collect data, involving all members of the Deaf Organization in Padang. As a result, more than a few deaf people have a good perception of the use of hearing aids, they agree that hearing aids are very helpful for communicating and carrying out daily activities and believe hearing aids can help the development of deaf children if used early.